A comparative study of excision with primary closure versus Limberg flap in pilonidal sinus - Meena, Omesh Kumar; Kalwaniya, Dheer Singh; Arya, Satya V.; Kuppuswami, Manikandan; Bajwa, Jaspreet Singh; Pradhan, Ravi S.; Narayan, Akshay; Mahadevan, Ranjith; Verma, Mukesh K. (International Surgery Journal, 2019)
Background: The term ‘pilonidal sinus’ describes a condition found in the natal cleft overlying the coccyx which is treated by excision. Methods: This study is a prospective study held in Department of general surgery, Safdarjung Hospital, New Delhi from October 2014 to April 2016 on 60 patients out of which 30 were controls (excision with primary closure) and 30 were taken as case (Limberg flap). Post-operative follow up was done till 6 months and complications were noted. The data was tabulated and SPSS version 17 was used for statistics. Results: Pilonidal sinus disease is common in age group 20 years and above and twice more common in males than females. Although operating time in Limberg flap is little more as compared to primary closure but insignificant. The post-operative pain in the long term follow up is less in the Limberg flap procedure, although in the initial post-operative period it is slightly higher as compared to primary closure. In Limberg flap procedure, post-operative complications like stitch line infection, seroma formation, wound dehiscence are low as compared to primary closure. Limberg flap require 2.27±0.52 days hospital stay as compared to 3.57±1.43 days in primary closure due to less post-operative complications. Recurrence rate is 3.33% in Limberg flap as compared to 26.67% in primary closure group. Conclusions: We recommend the Limberg flap method for primary pilonidal disease with low morbidity rates over primary closure.